Kewirausahaan Sosial Dalam Perspektif Ekonomi Islam - M. Hizbullah Hasibuan; Zuhrinal M. Nawawi (Masyarakat Ekonomi Syariah Bogor, 2023)
Business is a movement to satisfy needs that are overwhelmingly popular by many gatherings. Business venture today has encountered a change in direction from one benefit to another situated to be a social mission. Social business venture/social business exercises viewed as an option in taking care of monetary issues social. As a country where most individuals are Muslims what's more, considering the inescapable development of social business venture, then Islamic financial matters accompanies a perspective on data about the connection between friendly business and the upsides of Islamic regulation. Social exercises business when seen from the execution program plays practically a similar part with the point of Islamic financial matters itself with an end goal to increment development and financial prosperity. This study utilizes the writing survey strategy, in particular by gather a few ideas that are ordered from the exploration factors then, at that point, consolidated into another logical review. Moreover, the reason for making This examination is to add a little reference to the investigation of Social Entrepreneurship in the viewpoint of Islamic Economics. Keywords : Entrepreneurship, Islamic Economics, Social Entrepreneurship